O lúdico no processo de ensino e aprendizagem : concepções e práticas pedagógicas de professores dos iniciais do ensino fundamental - Silva, Janaina Monteiro da (2017)
The present dissertation is an investigative work that, in a qualitative approach, sought to answer the following question: "What are the pedagogical conceptions and practices that the teachers of the initial years have about the playful in the process of teaching and learning? the research presents as main objective: To investigate pedagogical conceptions and pedagogical practices of teachers about the playful in the process of teaching and learning of children from the initial years of elementary school. Four professors who worked in the 1st Phase of the 1st cycle and 1st Phase of the Second cycle of Human Training were part of the research. The method used was in the communicative perspective, based on the concept of the communicative action of the German philosopher and sociologist Jünger Habermas and on the dialogical action of the Brazilian educator Paulo Freire. In this research was used Communicative Research Methodology. The production of the information was performed according to the techniques and procedures of the methodology adopted. The techniques used were the communicative observations and the in - depth communicative interviews, which allowed a proximity of the reality of the investigated object, thus identifying the pedagogical conceptions and practices of the teachers of the initial years of elementary school about the playful in the process of teaching and learning of a municipal public school in the city of Rondonópolis, in Mato Grosso. The information collected was analyzed from the dimensions of the transforming and excluding elements, typical of the Communicative Research Methodology. This work reveals that the teachers recognize the importance of the playful in the process of learning of children, however, on the pedagogical practice in the playful perspective it was evidenced the lack of continuous formation to the teachers of the initial years of the elementary school of the researched school, fact this dialogued and explicitly criticized by all teachers participating in the research. The lack of continuous training reflects in the teaching practice, and this research proposes a reflection that implies (re) thinking the formation of teachers in the perspective of play. The research revealed, also as results, that theoretical subsidies are lacking on the understanding of the playful, which reflects in the pedagogical practice. In this sense, it makes it impossible to learn more effectively, that is, a learning that comes closest to the desired result. Effective learning from a playful perspective is only possible when it is planned, organized and committed to teaching content and when the objectives are worked for educational purposes. The pedagogical work in the ludic perspective reflects positively in the learning of the contents of teaching when thought for educational purposes and with seriousness by the teachers. Thus, we present, in this work, important subsidies for the reflection on the conceptions, the pedagogical practice and the continuous formation of teachers about the teaching work for a playful education.